The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1996
DOI: 10.1111/j.1476-5381.1996.tb15976.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of differential effects produced by ethanol on specific phospholipid biosynthetic pathways in rat hepatocytes

Abstract: 1 The aim of the present study was to investigate the effects of ethanol in vitro on the phospholipid biosynthetic pathways in hepatocytes isolated from the rat. We have used [methyl-"4C] products of the CDP-choline and CDP-ethanolamine pathways. Radioactivity in the metabolic intermediates of both pathways was significantly decreased and the amount of label in PE was reduced whilst that of PC was not modified. 3 In the presence of 4-methylpyrazole, an inhibitor of alcohol dehydrogenase (ADH) activity, ethanol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2000
2000
2007
2007

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…In the light of these findings, our previous experience with hepatic cells and research into the action of different xenobiotics on phospholipid metabolism [17,18] has prompted us to investigate the effect of HePC on the tumoral hepatic cell line HepG2. We studied its cytotoxic and cytostatic activity against HepG2 cells and examined its influence on de novo PC biosynthesis by using the precursor [methyl-14 C]choline as radioactive marker.…”
mentioning
confidence: 99%
“…In the light of these findings, our previous experience with hepatic cells and research into the action of different xenobiotics on phospholipid metabolism [17,18] has prompted us to investigate the effect of HePC on the tumoral hepatic cell line HepG2. We studied its cytotoxic and cytostatic activity against HepG2 cells and examined its influence on de novo PC biosynthesis by using the precursor [methyl-14 C]choline as radioactive marker.…”
mentioning
confidence: 99%
“…In the light of these findings, our previous experience with hepatic cells and research into the action of different xenobiotics on phospholipid metabolism [17,18] has prompted us to investigate the effect of HePC on the tumoral hepatic cell line HepG2. We studied its cytotoxic and cytostatic activity against HepG2 cells and examined its influence on de novo PC biosynthesis by using the precursor [methyl‐ 14 C]choline as radioactive marker.…”
mentioning
confidence: 99%
“…The formation of the phospholipid phosphatidylethanol (PEth) during ethanol exposure has been implicated in the pathogenesis of alcohol-induced organ damage [7]. Hepatic triacylglycerol accumulations have been described in chronic alcoholism [12]; however, reports on the effects of ethanol administration on the biosynthesis of cellular phospholipids are few and contradictory [4,10,16]. Several researchers have found that ethanol affects the incorporation and distribution of various exogenously supplied substrates in different ways.…”
mentioning
confidence: 99%